New results on the polarotactic behaviour of tabanids (tabanidae) (review) - Száz, Dénes; Herczeg, Tamás (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
The flying individuals of tabanids, similarly to other water-related and aquatic insects, detect water by the horizontally polarized light reflected from the water surface. The positive polarotaxis (i.e. the attraction to horizontally polarized light) of tabanids, discovered in 2008, made it possible to develop new tabanid traps based on reflected light polarization. The recent results on the polarotactic behaviour of tabanids, such as evidences for polarotactic host detection, contributed to the design of polarization tabanid traps. Furthermore, they made it possible to answer the old questions: What benefits the striped or spotted patterns of mammal coats do have? In this work we give a short summary about the most recent results in this topic.
Keywords: tabanid traps; polarization vision; imaging polarimetry; ecological trap